Reforming the Role of Auctioneers in Mortgage Execution in Indonesia: Legal Reform, Governance Transformation, and Its Contribution to Macroeconomic Resilience and Inclusive Institutions - Br. Turnip, Lydia Fransiscani (LP2M IAIN Palopo, 2025)
This study analyzes the current Indonesian auction system, focusing on execution auctions of mortgage rights. It identifies three key issues: a competence gap among State Auction Officials, where most lack legal backgrounds unlike their more legally proficient private counterparts; a substantial fiscal burden on the state due to a high volume of legal disputes and service inefficiencies; and a lack of legal certainty for auction winners. Using a normative juridical research method, the paper proposes a Hybrid Auction Authority Model (Delegative + National Certification). This model would allow the Directorate General of State Assets Management (DJKN) to remain the primary regulator while delegating the authority for complex execution auctions to certified private professionals, prioritizing notaries. The proposed reform, grounded in Max Weber's meritocracy theory and Hans Kelsen's pure theory of law, aims to enhance service efficiency, accelerate the resolution of non-performing loans, optimize state revenue, and strengthen governance by creating a more transparent and accountable system, thereby supporting national economic stability and regulatory transformation